Finite element analysis of structures through unified formulation - Carrera, Erasmo; Cinefra, Maria; Petrolo, Marco; Zappino, Enrico (Chichester, West Sussex : Wiley, 2014)
"This book deals with the Finite Element Method for the analysis of elastic structures such as beams, plates, shells and solids. The modern approach of Unified Formulation (UF), as proposed by the lead author, deals with the consideration of one-dimensional (beams), two-dimensional (plates and shells) and three-dimensional (solids) elements. Applications are given for structures which are typically employed in civil, mechanical, and aerospace engineering fields. Additional topics include mixed order elements, extension to layered composite structures, and the analysis of multifield problems involving mechanical, electrical and thermal loadings." --
9 One-Dimensional Models with a Physical Volume/Surface-Based Geometry and Pure Displacement Variables, the Lagrange Expansion Class9.1 Physical Volume/Surface Approach; 9.2 Lagrange Polynomials and Isoparametric Formulation; 9.3 LE Displacement Fields and Cross-section Elements; 9.4 Cross-section Multi-elements and Locally Refined Models; 9.5 Numerical Examples; 9.6 The Component-Wise Approach for Aerospace and Civil Engineering Applications; References; 10 Two-Dimensional Plate Models with Nth-Order Displacement Field, the Taylor Expansion Class
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Finite element method; Numerical analysis; MATHEMATICS / Numerical Analysis; Finite element method; Numerical analysis; Numerical analysis; Electronic books; Electronic books